2023
DOI: 10.3390/pharmaceutics15071961
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Skin Delivery and Stability of Vanillic and Ferulic Acids in Aqueous Enzymatically Extracted Glutinous Rice Husk by Nanostructured Lipid Carriers

Abstract: The present study aimed to develop nanostructured lipid carriers (NLCs) and evaluate their effectiveness in enhancing the delivery and stability of vanillic and ferulic acid in the aqueous enzymatic extract of glutinous rice husk using a 0.5% w/w cellulase solution (CE0.5). NLCs were developed using a high-pressure homogenization technique and characterized for their particle size, polydispersity index, and zeta potential. The entrapment efficiency, physical and chemical stability, release profile, skin permea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…The characterization results confirmed that the composition formulation of PRA-NLC and the preparation method were appropriate and robust. The small particle size (220.402 nm) could enhance the adhesiveness with the tissues and provide closer contact between the nanosystem and the skin [55]. The obtained polydispersity index value (PI) of 0.241 is within the optimal range for this type of formulation (0.1 to 0.25), showing a narrow size distribution and suggesting long-term physical stability [56].…”
Section: Discussionmentioning
confidence: 80%
“…The characterization results confirmed that the composition formulation of PRA-NLC and the preparation method were appropriate and robust. The small particle size (220.402 nm) could enhance the adhesiveness with the tissues and provide closer contact between the nanosystem and the skin [55]. The obtained polydispersity index value (PI) of 0.241 is within the optimal range for this type of formulation (0.1 to 0.25), showing a narrow size distribution and suggesting long-term physical stability [56].…”
Section: Discussionmentioning
confidence: 80%
“…The present study revealed that none of the formulations could permeate through the Strat-M ® membranes, designed to mimic human skin layers and reach the receptor chamber of the Franz diffusion cell apparatus. Therefore, there were no systemic side effects induced after the topical application of these formulations [ 45 ]. However, the skin retention profiles of PH were enhanced by the PH-loaded CANPs formulation, as illustrated in Figure 10 .…”
Section: Resultsmentioning
confidence: 99%
“…CANPs and PH-loaded CANPs were assessed for accelerated stability through 8 cycles of heating–cooling conditions and long-term storage at various temperatures (4 °C, 25 °C, and 45 °C) over a period of 90 days [ 45 ]. Each cycle of heating–cooling was composed of 4 °C for 24 h and then 45 °C for 24 h. Physical and chemical stability were examined after heating–cooling conditions and during long-term storage at 30, 60, and 90 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation